Disentangling the Quadruple System 1SWASP J093010.78+533859.5 - Gazeas, K. (Living Together: Planets, Host Stars and Binaries, 2015)
In the course of a photometric campaign undertaken at the University of Athens Observatory, the target 1SWASP J093010.78+533859.5 was observed and found to be a doubly-eclipsing quadruple system. This system was known as a contact binary since 2013, with an orbital period of 0.2277 days, and a detached binary lies along the same direction. Hipparcos astrometric observations confirm this finding, showing two stars with a common proper motion and an angular separation of only 1.7 arcsec. This favors the scenario of a true quadruple system, making 1SWASP J093010.78+533859.5 one of the very rare doubly-eclipsing quadruple systems known to date.